On the art history that we deserve - Jarque Soriano, Vicente (Estudios de Filosofía, 2018)
The essay is based on the need to keep developing alternatives to the official history of contemporary art. These alternatives would be the kind proposed from the point of view of feminism or queer theory. It takes the works of Douglas Crimp on Warhol as an example particularly brilliant and meaningful. In these works, facing the usual silence about his homosexuality, he presents Warhol's work, and espeficially most of his films, from a gay perspective, showing that without it, it is rather less intelligible. Although Crimp argues that these interpretations are derived from the so–called “cultural studies”, the conclusions are trying to point out that these texts, yet short in scope for the specific delimitation of its declared militancy, can be also understood (as well as those of others within the queer theory) as a legitimate and valuable contributions of a new historiography of contemporary art.